Characterization of Nd Radiogenic Isotope Signatures in Sediments From the Southwestern Atlantic Margin - Mantovanelli, Simone S.; Tassinari, Colombo C. G.; Mahiques, Michel M. De; Jovane, Luigi; Bongiolo, Everton (Frontiers in Earth Science, 2018)
Based on radiogenic isotope systems of neodymium (Epsilon Neodymium-ɛNd(0), 143Nd/144Nd, 147Sm/144Nd and Sm-Nd Depleted Mantle Model ages-TDM) from current and previous data from current and previous data of continental rocks and associated sediments, this work provides the provenance isotope signatures of Holocene sediments from the Southwestern Atlantic Margininof Core 7616 and Core 7620. The isotopic variability reported along the cores 7616 and 7620 are related to paleoceanographic and paleoclimatic changes. Further, we display the first Nd radiogenic isotope system distribution map of the study area. , this work provides provenance distribution of bulk sediment deposited those proxies inin southeastern South American upper margin, from ~7000 to 900 cal. yr BP. Here The map is the result of the principal component and clustering analyses of data compiled from the Ribeira belt, Luís Alves craton and Paraná basin rocks. Differences in we present a A Nd isotope isotopic signatures allowed the distinction between the sediment sources of the cores.a conspicuous large range of The variabilitydifference between them. Core 7616 exhibits ɛNd(0) average value of -10.5, which is similar to, TDM =1.4 Ga and 143Nd/144Nd =0.512103, while the Core 7620 shows ɛNd(0) average value of -17.5, TDM =1.8 Ga and 143Nd/144Nd =0.51177. The relative more radiogenic Nd ratios from the Core 7616 are associated to the contribution of sediments from the Paraná basin, nevertheless less radiogenic values are observed along the Core 7616 between ~2000 and 1800 cal. yr BP. We have attributed the lower Nd ratios, recorded during this interval, to the decreasing influence from the Rio de la Plata estuary in the Core 7616. Remarkable less radiogenic Nd ratios are also recorded in the Core 7620 during the late Holocene. The intensification of the NE winds and the South America Summer Monsoon (SASM) enhanced the terrigenous input from the Paraíba do Sul River and southwards sediment transport by the Brazil Current (BC), providing higher contribution of less radiogenic Data from Core metasediments from the Paraíba do Sul geotectonic domain to the Core 7620.